Letter (summary translation) - Carrillo, Wenceslao
1940-03-30 013-0088-001 SUMMARY OF LETTER FROM WENCESLAO CARRILLO, 30th March, 1940. He acknowledges receipt of our letter of 27th March, on tne question of the shooting of Ricardo Zabalza and Jose Gomez Osorio. He feels bound to raise with us the case of Rafael Henche, who was Lord Mayor of Madrid for more than two years of the war. Henche's daughter has written to Carrillo, begging him to do everything possible to prevent him from sharing the fate of Zabalza and Osorio. Carrillo does not know to whom to turn to get pressure exerted on Franco. Carlos Rubiera (Under-Secretary of State and President of the Madrid Civic Council) and Francisco de Toro (Member of the Cortes and head of the Madrid Purchasing Committee) are facing the same situation as Henche. The members of the National Council of Defence who are in London have twice approached the British and French Premiers and the President of the U.S.A., asking their intervention to call a halt to the shooting of men of whom it cannot be said that they are guilty of a criminal offence. No reply has been received. In these circumstances, nothing remains but recourse to the power of the Trade Unions. They ask the T.U.C. whether it will make approaches to see if it is possible to stop the shootings. The appeal is made in the name of the Spanish Socialist Party, the U.G.T. and the families of the potential victims. The Trade Unions have very definite power in England. Indubitably, a friendly warning from the British Government would influence the mind of Franco. He therefore hopes that the T.U.C. will do its utmost to see that the warning is given. The Franco regime has been in power in Spain for a year now, and is still shooting men for their political or Trade Union significance; Carrillo asks whether it is not time to put an end to these assasinations. He concludes by expressing the hope that a further approach will be made with a view to endeavouring to stop the shooting of Rafael Henche and many others. (signed) W. CARRILLO. C 292/946/13/88